Antecedents of stress in cross culture interaction among international students in University Utara Malaysia - Noraini, Mohamed Ali (2010)
Thousands of international students come to the University Utara Malaysia every year and from the moment they arrive they experience stress from multiple directions. This research project reported the result of the analysis conducted on data collected form 197 full time international undergraduate students under Colleges of Arts and Sciences in University Utara Malaysia (UUM). This study attempted to investigate the relationship between English language proficiency and stress in cross culture interaction among international students. This study also attempted to determine the relationship between misperception of culture values and stress in cross culture interaction. In addition, the demographics factors of gender and difference country of origin of study was investigated the difference level of stress in cross culture interaction among international students at UUM. Four research questions were examined: 1. Does English language proficiency have a significant relationship with stress in cross culture interaction among international students in UUM? 2. Does misperception of culture values have a significant relationship with stress in cross culture interaction among international students in UUM? 3. Do male and female international students have a different level of stress in cross culture interaction in UUM? 4. Does a student from different country of origin experience a different level of stress in cross culture interaction in UUM? This study was conducted on a sample of 197 international undergraduate students who complete measure questionnaire each instrument was scored collated with the demographic variable in a student‟s data set. All 197 students data set were subjected to a series of statistical analysis to conclude the determination of each hypothesis. The major finding of this study shows that stress in cross cultural interaction variables of dramatic had a major impact in social interaction. These studies also found that misperception of culture values are significant and positive relationship factors of stress in cross culture interaction among international undergraduate students in UUM. These results reveal that international students who lack of English language proficiency and perceived misperception of culture values seem to experience higher level of stress in cross culture interaction. There was no significance found among gender and difference country of origin with antecedent of stress in cross culture interaction. International male and female international students no difference level of stress in cross culture interaction. International students from ASIAN, Middle East and African also indicate no different in the level of stress in cross culture interaction at UUM. This study also provides recommendations are suggested.